T-MOSAiC 2022 myThaw data set - Julia Boike; Jennika Hammar; Maybrit Goldau; Norbert Anselm; Sarah Chadburn; Simon Zwieback; Julia Martin; Ekatarina N Abramova; Stéphanie Coulombe; Mariasilvia Giamberini; Fieke Rader; Guillaume Herment; et al. (PANGAEA, 2024)
The Terrestrial Multidisciplinary distributed Observatories for the Study of the Arctic Connections (T-MOSAiC) 2022 myThaw data set provides standardized measurements for permafrost thaw and the linked parameters snow depth, vegetation height, water level, soil texture and tree height as suggested by Boike et al. (2021). It contains measurements from 12 circumpolar permafrost sites where data was obtained using the myThaw app which is based on the user-friendly, multiparameter protocol for standardized monitoring of permafrost thaw from 2021. The data set contains detailed metadata for each site including data on the timing of data collection, geographical coordinates and land surface characteristics (vegetation, ground surface and water features).
In: Boike, Julia; Hammar, Jennika; Goldau, Maybrit; Miesner, Frederieke; Anselm, Norbert (2024): Circumarctic seasonal measurements of permafrost parameters (thaw depth, snow depth, vegetation and tree height, water level and soil properties) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.971787